STIMULUS EKSPOR TERHADAP KINERJA PERUSAHAAN-PERUSAHAAN BATIK - Darmansyah, Darmansyah; Soebagyo, Daryono (Universitas Muhammdaiyah Surakarta, 2010)
This study analyzes batik export performance in ex Karesidenan Surakarta. The Researcher links the export stimulus and toward export strategy and also to the impact of ex- port stimulus, and export strategy on export performance. The purpose of this study is to explain the relationship between export stimulus and toward the export strategy. This study is also aiming at explaining about the relation of the export stimulus, and export strategy toward export performance of Batik Company. The location of this study was in Ex Karesidenan of Surakarta. The total samples of this research were 108 companies but only 104 companies which could be investigated. The significant finding of this study is that the aid of market information from domestic/local government and importer and their political stability (environmental aspect) will improve the export performance. The strong willingness of the company managers to explore the existing resources owned by the companies will support the export performance (impulse factor).